2015
DOI: 10.1053/j.gastro.2014.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 Alters Localization of hMSH3, Leading to DNA Mismatch Repair Defects in Colorectal Cancer Cells

Abstract: Background & Aims Elevated microsatellite alterations at selected tetranucleotide repeats (EMAST) is the most common DNA mismatch repair (MMR) defect in colorectal cancers, observed in ~60% of specimens. This acquired genotype correlates with metastasis and poor outcome of patients, and is associated with intra-epithelial inflammation and heterogenous nuclear levels of the MMR protein hMSH3. Inflammation and accompanying oxidative stress can cause hMSH3 to change its intracellular location, but little is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 26 publications
(51 reference statements)
7
91
0
Order By: Relevance
“…As mentioned above, cumulative evidence supports the idea that the etiology of MSI-L/EMAST formation in cancer genome is the inflammation-induced loss of nuclear MSH3 in dividing cells (10,37,39). Therefore, it is reasonable to speculate that a sub-group of MSI-L/EMAST CRC may be associated with pathogenic infections of microbiota including Fusobacterium .…”
Section: Fusobacterium Infection Is Associated With Msi-l/emastsupporting
confidence: 55%
See 1 more Smart Citation
“…As mentioned above, cumulative evidence supports the idea that the etiology of MSI-L/EMAST formation in cancer genome is the inflammation-induced loss of nuclear MSH3 in dividing cells (10,37,39). Therefore, it is reasonable to speculate that a sub-group of MSI-L/EMAST CRC may be associated with pathogenic infections of microbiota including Fusobacterium .…”
Section: Fusobacterium Infection Is Associated With Msi-l/emastsupporting
confidence: 55%
“…These results suggest that some immunological and inflammatory responses are active in EMAST CRC. Later, Tseng-Rogenski et al demonstrated that in several cancer cell lines (37,39) inflammatory factors including oxidative stress (hydrogen peroxide), interleukin-6 (IL6) and prostaglandin E 2 (PGE 2 ) induce displacement of MSH3 from the nucleus to the cytoplasm, whereas the other MMR proteins do not displace. Repeated treatment of microsatellite stable colon cancer cell lines with IL6 induced EMAST.…”
Section: Characteristics Of Fusobacterium-associated Crcsmentioning
confidence: 99%
“…Recent studies suggest that E/L in non-MSI-H CRC may be caused by loss of MSH3 in a cancer cell due to the effects of tumor micro-environmental factors, such as hypoxia and/or inflammation, rather than genetic causes (17, 21, 28, 29, 30). Previously, we demonstrated that E/L in Stage II/III primary CRC is associated with a high risk for recurrent distant metastasis (21).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we were not able to correlate IL-6 polymorphisms with serum or intratumoral IL-6 expression levels which may lend insight on mechanisms of bevacizumab resistance. Nor were we able to determine interactions between microsatellite instability 8,49 , NSAID use, or inflammatory bowel disease, all of which may be affect the influence of IL-6 polymorphisms on outcomes. Functional studies are certainly needed to determine the significance of each examined genetic variant.…”
Section: Discussionmentioning
confidence: 99%
“…As initiators of pathologic inflammation, IL-6 and its downstream effector, STAT3 (signal transducer and activator of transcription-3), promote colorectal cancer (CRC) development 3,4 , invasion and metastasis 5–7 , by imposing genetic alterations in tumor cells 3,8 and facilitating immune tolerance within the microenvironment 6,9,10 . In colitis-associated cancer in vivo models, IL-6 enhances tumor cell proliferation and protects normal and malignant intestinal epithelial cells from apoptosis in a STAT3 dependent fashion.…”
Section: Introductionmentioning
confidence: 99%